Management of overlapping immune-related myocarditis, myositis, and myasthenia in a young patient with advanced NSCLC: a case report - Mariniello, Monica; Arrivi, Giulia; Tufano, Laura; Lauletta, Antonio; Moro, Mirella; Tini, Giacomo; Garibaldi, Matteo; Giusti, Raffaele; Mazzuca, Federica (Frontiers in Oncology, 2024)
Immunotherapy is increasingly used in advanced non-small-cell lung cancer (NSCLC), offering a significant anti-tumor response, as well as causing rising immune-related adverse effects. The incidence of immune checkpoint inhibitor-induced myocarditis–myositis–myasthenia gravis is increasing and particularly concerning due to its high mortality rate. Prompt recognition, diagnosis, and management are crucial. A 40-year-old patient, diagnosed with stage IV non-oncogene addicted lung adenocarcinoma, with nivolumab–ipilimumab–chemotherapy as first-line treatment, developed a rare myocarditis–myositis–myasthenia gravis overlap syndrome. Following the treatment, the patient presented with flu-like symptoms and chest pain and subsequently transferred to the cardiac intensive care unit. The physical examination revealed a visual acuity deficit, diplopia, ophthalmoparesis, ptosis, mydriasis, dysphagia, dyspnea, headache, nausea, dry mouth, asthenia, myalgia, and muscle weakness. Imaging and laboratory tests confirmed the triad, showing an elevation of hs-cTnI and CK and positive results for anti-SAE1 and anti-PL-7 Abs. ECG revealed ST segment elevation and RBBB. The echo showed hyperechogenicity of the inferolateral wall, pericardial detachment, and thickening. The cardiac MRI demonstrated hypokinesia, edema, subepicardial LGE, and pericardial effusion. Muscle biopsy revealed muscle fiber necrosis and regeneration with B and T lymphocytic endomysial inflammatory infiltrate and expression of MHC-I. Treatment with oral prednisone, pyridostigmine, and IV Igs was started due to poor clinical response followed by methylprednisolone. Despite stopping immunotherapy, the patient continued to benefit from it, as highlighted on subsequent re-evaluation CT scans by partial disease response, and as the patient was in complete remission, we decided to resume chemotherapy by omitting immunotherapy. At the radiological control following the four cycles of double CHT and during CHT maintenance, there was a further reduction of the disease. This report aims to raise awareness among physicians about these serious side effects. A multidisciplinary approach led to clinical improvement and early intervention, optimizing patient outcomes.